Relationship between the session-RPE and external measures of training load in youth soccer training - Marynowicz, J.; Kikut, K.; Lango, M.; Horna, D.; Andrzejewski, M. (The Journal of Strength and Conditioning Research, 2020)
The aim of this study was to identify the external training load (TL) markers (10 Hz Global Positioning System) that are most influential on the rating of perceived exertion (RPE) and session-RPE (sRPE) during youth soccer training. Data were collected from 18 youth soccer players during an 18-week in-season period. A total of 804 training observations were undertaken. We observed moderate to very large within-individual correlations between sRPE and measures of external load (r ranging from 0.36 to 0.76). Large, positive within-individual correlations were found between total covered distance, PlayerLoad, number of accelerations, and sRPE (r = 0.70, 0.64, and 0.62, respectively, p < 0.001). By contrast, small to moderate within-individual correlations were noted between RPE and measures of intensity (r ranging from 0.16 to 0.39). A moderate within-individual correlation was observed between high-speed running distance (HSR) per minute and RPE (r = 0.39, p < 0.001). The level of statistical significance was set at alpha = 0.05 for all tests. Two generalized estimating equation models were constructed, with RPE and sRPE as the response variables. The model identified by QIC for RPE contained 2 variables as follows: HSR per minute and distance in deceleration per minute, whereas sRPE was modeled with 3 predictors as follows: PlayerLoad, HSR, and distance in acceleration. The findings demonstrate that RPE does not reflect the intensity of a training session and that sRPE can be a useful, simple, and cost-effective tool for monitoring TL.